Assessment of Hospital Performance Using Quality of Care Indicators in Patients with Acute Coronary Syndrome - Sedra, Beshoy; Fakher, Mohamed; Sabri, Sherif; Elsherif, Ahmed; Kamer, Lamiaa Abu (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Global researchers have found a wide practice gap between the optimal care and actual care of patients with acute coronary syndrome (ACS). AIM: The main objective of the present study was to evaluate the quality of care provided to patients with ACS and compare our results to that of other similar studies and international standards. METHODS: A descriptive study was conducted using review of medical records and medical charts of new patients admitted and treated as ACS at the Department of Critical Care Medicine, Cairo University, from January 1, 2015, to December 31, 2020. For the purpose of the analysis, a set of highly predictive quality indicators was used. RESULTS: 967 patients were divided into two groups: 621 patients with acute ST-segment elevation myocardial infarction (STEMI) (mean age: 58.49 ± 11.45 years, 81.8% of males) and 34.9% presented to hospital in <4 h of symptom onset. Primary percutaneous coronary interventions (PCIs) were applied on 71.3% of cases (N = 443) and the mean “door-to-balloon” time was 78.8 min. In the first 24 h, acetylsalicylic acid (ASA), β-blockers, and angiotensin-converting enzyme inhibitors (ACE-I) or AR-blockers were administered in 100%, 65.9%, and 73.4% of the total eligible cases, respectively. At discharge, ASA, β-blockers, ACE-I/ARBs, and statins were prescribed in 90.8%, 78.3%, 82.8%, and 90.8%, respectively. 346 patients were with UA/NSTEMI (mean age 63±25.7 years, 69.4% male), while 21.7% of patients were presented to hospital after less than 4 hours of symptoms onset. Early PCIs were applied on 28.1% of cases (N = 97). In the first 24 h, ASA, β-blockers, and ACE-I or AR-blockers were administered in 100%, 78.3%, and 78.6% of the total eligible cases, respectively. At discharge, ASA, β-blockers, ACE-I/ARBs, and statins were prescribed in 93.4%, 83.2%, 81.2%, and 92.8%, respectively. In this study, a relation between different quality indicators with inhospital major adverse cardiac event and outcome was observed. CONCLUSION: There is still substantial work that lies ahead on the way to improve the uptake to evidence-based processes of care. We found some disparities between guidelines and clinical practice for ACS patients and a significant association between process indicators and inhospital outcomes. Our findings are potentially helpful for assessing and improving the quality of care for ACS patients in Egypt.